Association of serum magnesium level with microalbumin in urine of newly detected type-2 diabetes mellitus (Northern International Medical College Journal, 2018)
Background : Magnesium (Mg++) deficiency is associated with poor glycemic control and Mg++ supplementation lowers blood sugar, improves insulin sensitivity and delays diabetic complications such as diabetic nephropathy, diabetic neuropathy, diabetic retinopathy. Objective : This study was designed to know the status of serum Mg++ in type 2 diabetic subjects with microalbuminuria and normoalbuminuria.Methodology : This study was conducted at the Department of Laboratory Medicine (Clinical Pathology) in collaboration with BIRDEM General Hospital, Dhaka. In this study, serum magnesium level and urine microalbumin level of 120 newly detected type 2 diabetic patients were measured. Both levels were measured by biochemical auto analyzer (Siemens Dimension RL Max).Result : The mean microalbumin level was found 22.9±3.1 mg/L with range from 2-105 mg/L and the mean magnesium level was found 1.9±0.3 mg/dl with range from 1.5-2.4 mg/dl. Pearson’s correlation coefficient was -0.353 between serum magnesium level and urine microalbumin which was statistically significant (p value < 0.05). Therefore, there was a linear negative correlation between serum magnesium level and urine microalbumin.Conclusion : The present study revealed negative correlation between serum magnesium level and urine microalbumin.Northern International Medical College Journal Vol.9(2) Jan 2018: 291-294